The dynamics of intertextuality in Plutarch - Hirsch-Luipold, Rainer, 1967-; Schmidt, Thomas S.,; Vamvouri Ruffy, Maria, (Brill's Plutarch Studies ;, 2020)
The Dynamics of Intertextuality in Plutarch explores the numerous aspects and functions of intertextual links both within the Plutarchan corpus itself (intratextuality) and in relation with other authors, works, genres or discourses of Ancient Greek literature (interdiscursivity, intergenericity) as well as non-textual sources (intermateriality). Thirty-six chapters by leading specialists set Plutarch within the framework of modern theories on intertextuality and its various practical applications in Plutarch's Moralia and Parallel Lives . Specific intertextual devices such as quotations, references, allusions, pastiches and other types of intertextual play are highlighted and examined in view of their significance for Plutarch's literary strategies, argumentative goals, educational program, and self-presentation.